Examining Green Transformation In Nepalese Human Resource Management Practices - Joshi, Surendra Prasad; Ghimire, Binod (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: This study examines the variables influencing the implementation of environmentally friendly practices in organizations and to examinining the relationships between green transformational leadership, personal moral principles, green management of human resources, green commitment, with employee green behavior.Methodology: The study used a descriptive and causal research approach. The study used primary data with a questionnaire based on stratified random sampling techiniques, collected from a sample of 393 respondents consisting of employed personnel from both public and private sectors, encompassing banking and non-banking and college campuses. The study used Pearson’s correlation and regression analysis method to analyze data using the SPSS tool. Findings and Conclusion: The study reveals a signicant relationship of personal moral norms (0.800), green human resource management (0.749), green transformational leadership (.815), green commitment (.810) with employees green behaviour. These factors account for essential differences in employees’ involvement in environmentally conscious actions. The regression analysis determines the significant predictive capability of these parameters with green commitment being particularly prominent.Implications: These findings emphasize the solid empirical evidence of the study’s results, establishing a quantitative basis for the interrelatedness of personal beliefs, organizational practices, leadership styles, and employee participation in environmentally sustainable behaviors. The practical implications for organizations are enhanced by including quantitative evidence, highlighting the importance of dedication and strategic leadership in achieving long-lasting effects on a sustainable workplace. Further research in green behavior is essential, and the qualitative observation method is recommended for future researchers.